Different Dietary Protein Sources Affect the Intestinal Tight Junctions in the Colon of Mice - Rini , Dina Mustika; Pratiwi , Yunita Satya; Munarko , Hadi; Suzuki , Takuya (Future Science)
This study examined the effects of some dietary protein sources on intestinal barrier function in the colon of mice. 24 female ICR mice were randomly grouped into 4 groups (n=6) fed casein, soybean protein, whey protein concentrate (WPC), and egg white diet for 28 days. In this study, we collected the colon to analyzed the TJs proteins. Cecal contents were also collected to analyze the SCFAs. Mice fed with WPC showed the highest serum LBP concentration. Soybean and casein groups had the highest expression of occludin in the colon of mice. Total SCFAs were not significantly different among the groups. Correlation analysis showed that there is a positive correlation between ZO-1 and ZO-2 with total SCFAs. There is a positive correlation between plasma LBP concentration with claudin-3 expression in the colon of mice. These results confirmed that various dietary protein intake has a significant impact on the regulation of intestinal barrier integrity and SCFAs production might be contributing to the observation.